A design strategy and application of a low-temperature electrolyte film-forming additive for lithium metal batteries
Patent Information
- Application Number
- CN202611249512.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-16
AI Technical Summary
本发明的目的是解决目前在常温下表现良好的成膜添加剂在低温下性能表现急剧下降,导致电池低温性能变差的问题,设计了一种适用于锂金属电池低温电解液成膜添加剂的设计策略及应用
1、本发明的低温成膜添加剂的设计策略,通过较常温添加剂更低的LUMO能级,从而能够减弱低温动力学变慢对添加剂分解路径和SEI性能的影响,形成富无机的SEI,抑制锂枝晶的形成。
Smart Images

Figure CN122931040A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of secondary battery electrolyte technology, and relates to proposing a design strategy and application of a film-forming additive suitable for low-temperature electrolytes of lithium metal batteries, guiding the efficient design of low-temperature electrolytes for lithium metal batteries. Background Technology
[0002] Currently, the lithium-ion battery industry is developing rapidly, dominating the electronics market and electric vehicle sector. However, research shows that lithium-ion battery research has approached its theoretical specific capacity (372 mAh / g), insufficient to support the ever-increasing demand for extended driving range. Lithium metal, due to its lighter weight and lowest operating potential (-3.04 V compared to the standard hydrogen electrode), has attracted the attention of battery researchers. Benefiting from the physical and chemical properties of lithium metal, lithium metal batteries using lithium metal as the negative electrode can exhibit extremely high energy density and high discharge capacity. However, lithium metal negative electrodes experience various side reactions during cycling, such as dendrite growth and SEI damage, limiting the application of lithium metal batteries. Furthermore, many fields require batteries to operate in low-temperature environments, including defense applications, polar exploration, space exploration, and deep-sea exploration. These environments all require batteries to have good low-temperature performance. Lower temperatures affect the internal kinetics and reduction thermodynamics of the battery, including the bulk transport of lithium ions, the desolvation process of lithium ions, the formation of the SEI film, and the transport of lithium ions within the SEI film. Previous studies have focused more on the impact of low temperatures on kinetics, with relatively less attention paid to thermodynamics. However, low temperatures affect the reduction pathway of the electrolyte on the lithium metal anode surface, leading to differences in reduction products. Therefore, minimizing the impact of low temperatures on film-forming additives is crucial for the design of lithium metal battery electrolytes. Taking room-temperature-friendly additives such as fluoroethylene carbonate (FEC) as an example, studies have shown that compared to the composition of the SEI film at room temperature, the content of fluorine-containing substances in the SEI formed on the lithium metal anode surface decreases significantly at low temperatures, mainly manifested as a decrease in LiF content. The content of other inorganic substances also decreases, while the content of organic substances increases. Therefore, the SEI film at low temperatures exhibits low lithium-ion mobility, poor cycle stability, resulting in poor cycle life and low lithium deposition / stripping efficiency. Therefore, it is extremely important to define design strategies for film-forming additives suitable for low-temperature electrolytes in lithium metal batteries. To improve the stability of SEI at low temperatures, we need to select and design a film-forming additive that performs well at low temperatures and reduce the SEI changes caused by slow kinetics. Here, we propose to further introduce the substitution of negatively charged groups into the additive based on room temperature-friendly additives to reduce the LUMO energy level of the additive, improve the low temperature adaptability of the additive, and improve the composition and cycling stability of SEI at low temperatures. Summary of the Invention
[0003] 1. The technical problem the invention aims to solve. The purpose of this invention is to address the problem that film-forming additives, which perform well at room temperature, experience a sharp decline in performance at low temperatures, leading to deterioration in battery low-temperature performance. This invention proposes a design strategy and application for film-forming additives suitable for low-temperature electrolytes in lithium metal batteries. By rationally designing and lowering the LUMO energy level of conventional film-forming additives, this invention improves their low-temperature adaptability and reduces the performance difference between room-temperature and low-temperature SEIs. It achieves the induction of inorganic-rich (LiF, Li3N, Li2S, and Li2O) SEI films with excellent overall performance, providing superior low-temperature charge-discharge performance. This has significant reference value for the design of low-temperature electrolytes for lithium metal batteries and the practical application of lithium metal batteries.
[0004] 2. Technical Solution To achieve the above objectives, the technical solution provided by the present invention is as follows: This invention discloses a design strategy for a film-forming additive suitable for low-temperature lithium metal batteries, which exhibits superior performance compared to conventional film-forming additives in low-temperature environments. The performance and design strategy of this additive are as follows.
[0005] The low-temperature film-forming additives need to contain highly electronegative elements or groups such as fluorine, nitrogen, and sulfur to achieve a lower LUMO energy level.
[0006] The number of strongly electronegative elements or groups contained in the low-temperature film-forming additive should be greater than 1.
[0007] The main component of the low-temperature film-forming additive should be a film-forming additive that performs well at room temperature, such as one of ethylene carbonate (EC), vinylene carbonate (VC), propylene carbonate (PC), fluoroethylene carbonate (FEC), or vinylene sulfate (ES).
[0008] The volume ratio of the film-forming additive in the electrolyte should be less than 10%.
[0009] The present invention relates to a design strategy and application of a low-temperature electrolyte film-forming additive for lithium metal batteries. This low-temperature film-forming additive can form a high-performance interface film on the surface of a lithium metal anode in a low-temperature environment, providing excellent cycle stability and deposition / stripping efficiency.
[0010] The aforementioned low-temperature film-forming additive enables lithium metal batteries to operate in a temperature range of -60°C. o C~30 o C.
[0011] The technical solution of this invention has the following advantages: 1. The design strategy of the low-temperature film-forming additive of the present invention, through the lower LUMO energy level than the room temperature additive, can reduce the impact of the slowed low-temperature kinetics on the additive decomposition path and SEI performance, form an inorganic-rich SEI, and suppress the formation of lithium dendrites.
[0012] 2. The design strategy of the low-temperature film-forming additive of the present invention has more inorganic elements and inorganic groups, which can not only improve the melting point and viscosity of the additive, thereby effectively improving electrode wettability and improving the composition and performance of SEI at low temperature, but also reduce the solvation effect of inorganic elements with lithium ions and lower the desolvation energy barrier of lithium ions.
[0013] 3. The design strategy of the low-temperature film-forming additive of the present invention can be used in high-energy-density lithium metal batteries and can be stably cycled at low temperatures. The negative electrode of the lithium metal battery is lithium metal, and the positive electrode material is one or more of lithium iron phosphate, lithium cobalt oxide, lithium titanate, lithium manganese oxide, lithium nickel oxide, nickel cobalt manganese ternary, nickel cobalt aluminum ternary, sulfur, oxygen, carbon dioxide, and air. Furthermore, the electrolyte has the advantages of high voltage resistance, high performance, low temperature resistance and low cost, and has extremely high commercialization prospects. Attached Figure Description
[0014] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0015] Figure 1 For Example 1, a room-temperature friendly film-forming additive (FEC) control group and a low-temperature friendly film-forming additive (DFEC) experimental group were used at 30°C. o C and -20 o Lithium deposition / stripping efficiency diagram under C.
[0016] Figure 2 Example 2 used a room-temperature friendly film-forming additive (FEC) control group and a low-temperature friendly film-forming additive (DFEC) experimental group at 30°C. o C and -20 o The cycle performance diagram of a lithium copper battery under condition C.
[0017] Figure 3 Example 3 used a room-temperature friendly film-forming additive (FEC) control group and a low-temperature friendly film-forming additive (DFEC) experimental group at 30°C. o C and -20 o Time-voltage diagram of a lithium-lithium symmetric battery under condition C.
[0018] Figure 4 SEM images of lithium deposition morphology analysis in Example 4 using the room temperature friendly film-forming additive (FEC) control group and the low temperature friendly film-forming additive (DFEC) experimental group. Detailed Implementation
[0019] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.
[0020] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.
[0021] This invention relates to a film-forming additive for low-temperature lithium metal batteries, which is a difluorinated fluorinated carbonate additive. Compared with the conventional additive FEC, this film-forming additive has a molecular structure with more fluorine (F) elements, exhibits a lower LUMO energy level, and can form an inorganic-rich SEI. We introduce two additives with different degrees of fluorination into an ether-based electrolyte that stabilizes the lithium metal anode, reducing the influence of other components in the electrolyte on the lithium metal anode.
[0022] The low-temperature film-forming additive in this invention is a polyfluorinated carbonate additive, preferably one of cis-difluoroethylene carbonate, trans-difluoroethylene carbonate, trifluoroethylene carbonate, and methyltrifluoroethyl carbonate, with trans-difluoroethylene carbonate being the most preferred. The volume ratio of the additive is 1-15%, preferably 10%, and will not be described in detail in the following examples. Example
[0023] An ether-based main electrolyte was prepared (0.6 mol / L LiTFSI and 0.4 mol / L LiNO3 in 1,3-dioxolane (DOL) / ethylene glycol dimethyl ether (DME), v / v = 1:1). Subsequently, film-forming additives were introduced to prepare a control group (room temperature excellent additive FEC) and an experimental group (low temperature excellent additive DFEC) (0.6 mol / L LiTFSI and 0.4 mol / L LiNO3 in (1,3-dioxolane)DOL / (ethylene glycol dimethyl ether)DME / (fluoroethylene carbonate)FEC / (difluoroethylene carbonate)DFEC, v / v = 8:2:1).
[0024] A lithium-copper half-cell was assembled using the above-mentioned electrolyte, lithium sheet, copper sheet, and separator, and a 1 mA cm⁻¹ solution was used.-2 The current density is at normal temperature (30 °C) and low temperature (-20 °C) environments. o C) Lithium deposition / stripping efficiency testing was performed, such as Figure 1 As shown, in 30 o C, the lithium copper battery containing the control group-FEC exhibited higher lithium deposition / stripping efficiency (99.26% vs 98.97%) and lower polarization voltage and nucleation overpotential compared to the experimental group-DFEC. However, at -20 o C. The lithium-copper battery containing the experimental group-DFEC exhibited higher lithium deposition / stripping efficiency (99.36% vs 98.33%) and lower polarization voltage and nucleation overpotential compared to the control group-FEC. This embodiment demonstrates that although the DFEC based on the low-temperature film-forming additive design strategy proposed in this invention has poor lithium deposition / stripping performance at room temperature, it exhibits comprehensive advantages at low temperatures, indicating that it can stabilize the lithium metal anode at low temperatures and improve the cycle performance of lithium metal batteries. Example
[0025] An ether-based main electrolyte was prepared (0.6 mol / L LiTFSI and 0.4 mol / L LiNO3 in 1,3-dioxolane (DOL) / ethylene glycol dimethyl ether (DME), v / v = 1:1). Subsequently, film-forming additives were introduced to prepare a control group (room temperature excellent additive FEC) and an experimental group (low temperature excellent additive DFEC) (0.6 mol / L LiTFSI and 0.4 mol / L LiNO3 in (1,3-dioxolane)DOL / (ethylene glycol dimethyl ether)DME / (fluoroethylene carbonate)FEC / (difluoroethylene carbonate)DFEC, v / v = 8:2:1).
[0026] A lithium-copper half-cell was assembled using the above-mentioned electrolyte, lithium sheet, copper sheet, and separator, and a 1 mA cm⁻¹ solution was used. -2 The current density is at normal temperature (30 °C) and low temperature (-20 °C) environments. o C) Battery cycle performance was tested at a discharge deposition capacity of 1 mAh cm⁻¹. -2 The charging cutoff voltage is 1 V. For example... Figure 2 As shown, in 30 o C, the lithium copper battery containing the control group -FEC showed higher lithium deposition / stripping efficiency in the early stages of cycling than the experimental group -DFEC, but the experimental group -DFEC showed better cycle stability. However, at -20 oC. The lithium-copper battery containing the experimental group-DFEC exhibits higher lithium deposition / stripping efficiency and better cycle stability than the control group-FEC. This embodiment demonstrates that the DFEC based on the low-temperature film-forming additive design strategy proposed in this invention exhibits better cycle stability at room temperature and demonstrates comprehensive advantages at low temperatures, indicating that it can stabilize the lithium metal anode at low temperatures and improve the cycle performance of lithium metal batteries. Example
[0027] An ether-based main electrolyte was prepared (0.6 mol / L LiTFSI and 0.4 mol / L LiNO3 in 1,3-dioxolane (DOL) / ethylene glycol dimethyl ether (DME), v / v = 1:1). Subsequently, film-forming additives were introduced to prepare a control group (room temperature excellent additive FEC) and an experimental group (low temperature excellent additive DFEC) (0.6 mol / L LiTFSI and 0.4 mol / L LiNO3 in (1,3-dioxolane)DOL / (ethylene glycol dimethyl ether)DME / (fluoroethylene carbonate)FEC / (difluoroethylene carbonate)DFEC, v / v = 8:2:1).
[0028] The above-mentioned electrolyte, lithium sheet, copper sheet, and separator were used to assemble lithium-lithium symmetric batteries, and the results were measured at 1 mA cm⁻¹. -2 Current density and 1 mAh cm -2 At room temperature (30) o C) Low temperature (-20) o C) Perform long-cycle testing. Results are as follows: Figure 3 As shown, the lithium-lithium symmetric cell using the control group-FEC at 30 o At C, it exhibited lower polarization voltage and nucleation overpotential than the experimental group -DFEC, but the experimental group -DFEC showed superior cycle life. At -20... o At temperature C, the experimental group -DFEC exhibited a lower polarization voltage and nucleation overpotential. This example demonstrates that the low-temperature film-forming additive proposed in this invention exhibits better performance at low temperatures than lithium metal anodes at -20°C. o The C-type loop is more stable and efficient, exhibiting excellent loop performance. Example
[0029] An ether-based main electrolyte was prepared (0.6 mol / L LiTFSI and 0.4 mol / L LiNO3 in 1,3-dioxolane (DOL) / ethylene glycol dimethyl ether (DME), v / v = 1:1). Subsequently, film-forming additives were introduced to prepare a control group (room temperature excellent additive FEC) and an experimental group (low temperature excellent additive DFEC) (0.6 mol / L LiTFSI and 0.4 mol / L LiNO3 in (1,3-dioxolane)DOL / (ethylene glycol dimethyl ether)DME / (fluoroethylene carbonate)FEC / (difluoroethylene carbonate)DFEC, v / v = 8:2:1).
[0030] The above-mentioned electrolyte, lithium sheet, copper sheet, and separator were used to assemble a lithium-copper half-cell, which was then tested at room temperature (30°C). o C) and low temperature (-20) o Cycling and deposition were performed under condition C. Deposition was performed after 30 cycles, with a deposition rate set to 2 mAh cm⁻¹. -2 The obtained SEM image is as follows Figure 4 As shown, at room temperature, the lithium deposition morphology of the control group-FEC and the experimental group-DFEC is similar. However, at low temperature, the experimental group-DFEC exhibits a superior morphology, with a more uniform and dense distribution, a smoother morphology, and larger particles. The control group-FEC, on the other hand, shows many lithium dendrites. This example demonstrates that the low-temperature film-forming additive proposed in this invention is more suitable for use at low temperatures and exhibits superior low-temperature performance compared to conventional film-forming additives.
[0031] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A design strategy and application of a film-forming additive suitable for low-temperature electrolytes in lithium metal batteries, characterized in that, The design strategy includes: using organic compounds with low melting points, low unoccupied molecular orbital (LUMO) energy levels, and multiple inorganic element characteristics as functional molecules, and screening them as film-forming additives for low-temperature electrolytes; wherein, the low LUMO energy level means that the LUMO energy level of the functional molecule is lower than that of the LUMO energy level of the electrolyte base solvent, so that it can be used in low-temperature electrolytes below -20°C. o At low temperature C, the functional molecules can preferentially undergo electrochemical reduction on the lithium metal anode surface before the basic solvent, and form a solid electrolyte interface film rich in inorganic components in situ.
2. The design strategy according to claim 1, characterized in that: The low LUMO energy level is achieved by introducing at least one inorganic group or element selected from fluorine-containing groups, nitrogen-containing groups, sulfur-containing groups, or boron-containing groups into the molecular structure of the organic compound.
3. The design strategy according to claim 1, characterized in that: The aforementioned multiple inorganic element characteristic refers to the fact that the molecular structure of the organic compound simultaneously contains at least two inorganic groups or elements selected from fluorine-containing groups, nitrogen-containing groups, sulfur-containing groups, or boron-containing groups.
4. The design strategy according to claim 1, characterized in that: The low LUMO energy level is relative to the LUMO energy level of conventional lithium-ion battery room-temperature film-forming additives.
5. The design strategy according to claim 1, characterized in that, The low LUMO level specifically refers to the LUMO level of the functional molecule being more than 0.2 eV lower than the LUMO level of ethylene carbonate.
6. The design strategy according to claim 1, characterized in that: The inorganic-rich solid electrolyte interface film has high ionic conductivity and high interface stability, which can promote the interfacial transport of lithium ions at low temperatures and inhibit the growth of lithium dendrites.
7. A film-forming additive suitable for low-temperature electrolytes in lithium metal batteries according to any one of claims 1-6, characterized in that: This film-forming additive enables lithium metal batteries to operate at low temperatures, with an operating temperature range of -60°C. o C~30 o C.